Morphological, biochemical and physiological traits of upper and lower canopy leaves of European beech tend to converge with increasing altitude - Rajsnerová, Petra; Klem, Karel; Holub, Petr; Novotná, Kateřina; Večeřová, Kristýna; Kozáčiková, Michaela; Rivas-Ubach, Albert; Sardans, Jordi; Marek, Michal V; Peñuelas, Josep; Urban, Otmar (Tree physiology, 2015)
The present work has explored for the first time acclimation of upper versus lower canopy leaves along an altitudinal gradient. We tested the hypothesis that restrictive climatic conditions associated with high altitudes reduce within-canopy variations of leaf traits. The investigated beech (Fagus sylvatica L.) forest is located on the southern slope of the Hrubý Jeseník Mountains (Czech Republic). All measurements were taken on leaves from upper and lower parts of the canopy of mature trees (>85 years old) growing at low (400 m above sea level, a.s.l.), middle (720 m a.s.l.) and high (1100 m a.s.l.) altitudes. Compared with trees at higher altitudes, those growing at low altitudes had lower stomatal conductance, slightly lower CO(2) assimilation rate (A(max)) and leaf mass per area (LMA), and higher photochemical reflectance index, water-use efficiency and Rubisco content. Given similar stand densities at all altitudes, the different growth conditions result in a more open canopy and higher penetration of light into lower canopy with increasing altitude. Even though strong vertical gradients in light intensity occurred across the canopy at all altitudes, lower canopy leaves at high altitudes tended to acquire the same morphological, biochemical and physiological traits as did upper leaves. While elevation had no significant effect on nitrogen (N) and carbon (C) contents per unit leaf area, LMA, or total content of chlorophylls and epidermal flavonoids in upper leaves, these increased significantly in lower leaves at higher altitudes. The increases in N content of lower leaves were coupled with similar changes in A(max). Moreover, a high N content coincided with high Rubisco concentrations in lower but not in upper canopy leaves. Our results show that the limiting role of light in lower parts of the canopy is reduced at high altitudes. A great capacity of trees to adjust the entire canopy is thus demonstrated.
Keywords: Photosynthesis; Plant Leaves; Nitrogen; dusík; světlo; Phenotype; Ribulose-Bisphosphate Carboxylase; listy rostlin; Plant Stomata; Light; ribulosa-1,5-bisfosfát-karboxylasa; Carbon; Carbon Dioxide; Altitude; fenotyp; buk (rod); voda; oxid uhličitý; průduchy rostlin; Water; uhlík; fotosyntéza; Fagus; nadmořská výška